1990
DOI: 10.1144/gsl.mem.1990.012.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoclimatic constraints for palaeozoic Palaeolatitudes of Laurentia and Euramerica

Abstract: Palaeozoic lithic palaeoclimatic data were plotted at the series or stage level for Laurentia (North America) andEuramerica. Their distribution was used to infer the extent of humid and arid climatic belts across the continent for specified time intervals. Climatic data are potentially useful for constraining palaeolatitudes for times when zonal atmospheric circulation remains the dominant pattern. Arid lithic indicators (evaporites, carbonate oolite) and humid indicators (coal, bauxite) were constrained to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 21 publications
10
123
0
Order By: Relevance
“…Ever since Barrell's interpretation (1916), paleoclimatic indicators confirmed this view (e.g., Woodrow et al, 1973;Heckel and Witzke, 1979;Woodrow, 1985;Witzke and Heckel, 1988;Sageman et al, 2003;Cressler, 2006;Cressler et al, 2010), and a consensus on the seasonal wet-and-dry climate model for the Devonian of the Euramerican coastal plains exists. The paleolatitude combined with the proximity of large continental areas (as well Euramerica as Gondwana) play an important role in determining the potential for an intense monsoonal circulation over Euramerica (Witzke, 1990). Given the significant influence of astronomical forcing on modern monsoonal systems, it is highly probable that also during the Devonian period, Milanković cycles influenced the climatic factors controlling the detrital inputs to the Rhenohercynian basin (i.e., wind and precipitation) and/or of carbonate productivity, both affecting the MS signal (Riquier et al, 2010).…”
Section: Magnetic Susceptibility As a Climate Proxymentioning
confidence: 99%
“…Ever since Barrell's interpretation (1916), paleoclimatic indicators confirmed this view (e.g., Woodrow et al, 1973;Heckel and Witzke, 1979;Woodrow, 1985;Witzke and Heckel, 1988;Sageman et al, 2003;Cressler, 2006;Cressler et al, 2010), and a consensus on the seasonal wet-and-dry climate model for the Devonian of the Euramerican coastal plains exists. The paleolatitude combined with the proximity of large continental areas (as well Euramerica as Gondwana) play an important role in determining the potential for an intense monsoonal circulation over Euramerica (Witzke, 1990). Given the significant influence of astronomical forcing on modern monsoonal systems, it is highly probable that also during the Devonian period, Milanković cycles influenced the climatic factors controlling the detrital inputs to the Rhenohercynian basin (i.e., wind and precipitation) and/or of carbonate productivity, both affecting the MS signal (Riquier et al, 2010).…”
Section: Magnetic Susceptibility As a Climate Proxymentioning
confidence: 99%
“…The Desmoinesian coals of the Eastem Interior Basin accumulated at tropical latitudes (Witzke, 1990;Heckel, 1994Heckel, , 1995 and appear to have consisted of widespread topogenous to soligenous mires or mii-e complexes, relatively undivided by extrabasinal secondary and tertiary drainages. If a 10:1 peat-to-coal compaction ratio is assumed, the only modem peats with comparable thicknesses to these Desmoinesian paleomires are the ombrogenous mires of Indonesia.…”
Section: Comparison To Modem Thick Peatlandsmentioning
confidence: 99%
“…0° (Witzke, 1990) Marathon Ouachita Figure 18. Paleogeography of Desmoinesian peatlands in eastern and middle United States (modified from information in Heckel, 1980;Thomas, 1989;Johnson et al, 1988;Donaldson and Eble, 1991).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The siliciclastic muds derived from the erosion of tectonic highlands to the south-east in New York State were deposited in the northern, apparently blind, end of the Appalachian Foreland Basin whose axis trended approximately north-east±south-west. These sediments accumulated in a shallow subtropical muddy sea approximately 15±20 degrees south of the palaeoequator (Ziegler et al 1977;Witzke 1990). Brett (1983a, b) concluded that the local facies strike in western New York and Ontario was approximately east±west, paralleling the modern Niagara escarpment outcrop belt.…”
Section: O V E R V I E W O F S T R a T I G R A P H Ymentioning
confidence: 99%